The disciplinary guaranties in the Algerian public Function statute: a legal framework Les garanties disciplinaires dans le statut de la fonction publique algérienne: le cadre juridique - DEBIH, Hatem (The journal of Teacher Researcher of Legal and political Studies, 2025)
At any public administration; public officials while they perform their duties may commit disciplinary faults, even though, they can’t be judged without procedures, which may increase arbitrary rules, the Algerian general statute of public function stipulates the disciplinary procedures and guaranties in order to protect the public official’s rights, these guaranties are so important, because they ensure the protection of public official from encroachment and abuse of the disciplinary authority while exercising the disciplinary procedures in accordance with the law, this research paper aimed at identify the disciplinary guaranties for the public official, their legal nature and sources, also their different types and stages, the public official has the right to defend himself before any procedure against him